Modern homophobia among heterosexual Romanian adults: the roles of sexual orientation beliefs, religiosity, perceived social roles, and social media use - Lăzărescu, Georgiana; Karner-Hutuleac, Adina; Maftei, Alexandra (Frontiers in Psychology, 2023)
The present study aimed to examine some potential predictors of homophobia against lesbians and gay individuals. Our sample comprised 722 heterosexual participants aged 18–74, mostly women (self-reported gender; 224 men and 498 women) with various educational backgrounds (i.e., High School, Bachelor’s, and Master’s degrees). Participants filled in self-reported scales measuring sexual orientation beliefs (incremental vs. entity views), religiosity, social media use, and perceived gender-transcendent social roles. Correlation analyses and multiple regression models were computed separately for men and women. For all participants, homophobia against lesbians (HAL) was negatively associated with participants’ age, religiosity, and gender-transcendent social roles and positively with incremental views about sexuality. However, only in the case of women was HAL positively related to social media use. Next, for both men and women, homophobia against gay individuals (HAG) was negatively related to age, religiosity, and gender-transcendent social roles. However, only in the case of women, HAG was positively related to social media use online and incremental views about sexuality. In the case of men, the most significant predictor of HAL was the perceived gender-transcendent social roles and HAG – perceived gender-linked social roles. For women, perceived gender-linked social roles were the most significant predictor of both HAL and HAG. Results are discussed regarding their use for interventions aimed at reducing homophobia among heterosexual individuals.